2017
DOI: 10.5194/acp-2017-52
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Investigating Diesel Engines as an Atmospheric Source of Isocyanic Acid in Urban Areas

Abstract: <p><strong>Abstract.</strong> Isocyanic acid (HNCO), an acidic gas found in tobacco smoke, urban environments and biomass burning-affected regions, has been linked to adverse health outcomes. Gasoline- and diesel-powered engines and biomass burning are known to emit HNCO and hypothesized to emit precursors such as amides that can photochemically react to produce HNCO in the atmosphere. Increasingly, diesel engines in developed countries like the United States are requi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 30 publications
(85 reference statements)
2
21
0
Order By: Relevance
“…Emissions of nitrogen‐containing VOCs such as HCN and HNCO are known to be highly variable depending on the type and origin of the fuel. Increasing the nitrogen content of a biogenic fuel type by 1% can increase the emission of nitrogen‐containing VOCs by 2–6% (Coggon et al, ), and the inclusion of a diesel oxidation catalyst to a diesel engine can increase the HNCO NEMR by a factor of 30 (Jathar et al, ). Total isocyanate concentrations measured after burning various plastics can vary by 3 orders of magnitude depending on the precursor fuel nitrogen content, and accordingly, plastics containing no nitrogen do not produce any isocyanates (Blomqvist et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Emissions of nitrogen‐containing VOCs such as HCN and HNCO are known to be highly variable depending on the type and origin of the fuel. Increasing the nitrogen content of a biogenic fuel type by 1% can increase the emission of nitrogen‐containing VOCs by 2–6% (Coggon et al, ), and the inclusion of a diesel oxidation catalyst to a diesel engine can increase the HNCO NEMR by a factor of 30 (Jathar et al, ). Total isocyanate concentrations measured after burning various plastics can vary by 3 orders of magnitude depending on the precursor fuel nitrogen content, and accordingly, plastics containing no nitrogen do not produce any isocyanates (Blomqvist et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Isocyanic acid (HNCO) is another highly toxic, long‐lived gas (lifetime of days to decades; Borduas et al, ) emitted from BB with similar anthropogenic and biogenic sources as HCN. Urban sources of HNCO are attributed to primary activity such as automotive emission (Jathar et al, ), residential heating (BB) (Woodward‐Massey et al, ), and industrial processes, for example, from brick kiln emissions (Sarkar et al, ). A secondary source of HNCO is amide oxidation (e.g., Borduas et al, ), which has been observed at a suburban site in Mohali, India (Chandra & Sinha, ), and in an urban environment in Pasadena, California (Roberts et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Emissions of HNCO into the atmosphere have been quantied from a variety of anthropogenic and natural sources through laboratory experiments and eld measurements. The primary emission sources include biomass burning, 19,20,22,[26][27][28][29] fossil fuel combustion (coal, gasoline, and diesel), 19,[30][31][32][33][34][35][36][37] and cigarette smoke. 19,38,39 The secondary production of HNCO, through the oxidation of amines and amides is also a potential source.…”
Section: Sourcesmentioning
confidence: 99%
“…74 In these systems, urea thermally decomposes into NH 3 and HNCO. 35,49,75 The reaction proceeds as follows (R7): 35 (R7) HNCO is then hydrolysed to produce NH 3 and CO 2 (R9). NH 3 acts as the reducing agent for NO and NO 2 yielding N 2 and H 2 O.…”
Section: Fossil Fuel Combustionmentioning
confidence: 99%
“…6 VOCs are ubiquitous in our environment and are emitted or generated from many different sources. 12 ICA is a strong organic acid that, together with other pollutants, has been found in fire smoke, 13,14 in diesel emissions, 15,16 and in emissions from heated products that contain urea-formaldehyde resins as binders. 7 Monoisocyanates such as isocyanic acid (ICA) and methyl isocyanate (MIC) are one type of VOCs that could be generated during heat degradation or combustion of nitrogen-containing products.…”
Section: Introductionmentioning
confidence: 99%